Molecular Switches and Motors on Surfaces - Pathem, Bala Krishna; Claridge, Shelley A.; Zheng, Yue Bing; Weiss, Paul S. (Annual Review of Physical Chemistry, 2013)
Molecular switches and motors respond structurally, electronically, optically, and/or mechanically to external stimuli, testing and potentially enabling extreme miniaturization of optoelectronic devices, nanoelectromechanical systems, and medical devices. The assembly of motors and switches on surfaces makes it possible both to measure the properties of individual molecules as they relate to their environment and to couple function between assembled molecules. In this review, we discuss recent progress in assembling molecular switches and motors on surfaces, measuring static and dynamic structures, understanding switching mechanisms, and constructing functional molecular materials and devices. As demonstrative examples, we choose a representative molecule from three commonly studied classes including molecular switches, photochromic molecules, and mechanically interlocked molecules. We conclude by offering perspectives on the future of molecular switches and motors on surfaces.
Keywords: oligo(phenylene ethynylene)